Safety and efficacy of colonic EMR in a district general hospital. (13th March 2011) - Subhani, J; Lindo, D; Gertner, D; Warburton, R; Alsanjari, N; Abdullah, A
Abstract : Introduction: Virtually all published data on colonic endoscopic mucosal resection (EMR) comes from expert centres and yet it is likely that the majority of these procedures are performed outside these hospitals. At our centre, like many others, a single endoscopist (JMS) provides an EMR service that the other eight colonoscopists have referred to over the last 5+ years. We evaluated its use, efficacy and safety. Methods: Sessile and flat colonic polyps >10 mm assessed for resection were identified prospectively and follow-up data collection started. These would include referrals to the EMR service as well as lesions resected by JMS at the index endoscopy. Multi-session resections were done within 3 months. Standard endoscopic follow-up was at 3 months for piecemeal resections. For en-bloc resections follow-up was at a minimum as per BSG guidelines but additional surveillance procedures may have been undertaken due to patient and histological factors. All initial resections were performed by JMS with Olympus equipment the majority by lift and cut method. Argon was used after piecemeal resections as appropriate. Results: 340 lesions were assessed in 303 patients. 31 did not undergo resection (21 judged T2+ stage, 3 due to position, 4 due to size and 3 due to non-adenomatous pathology). 296 required one session, 11 two sessions and 2 three sessions. Clearance was achieved at the initial session in 93% of polyps > = 20 mm. Safety: The following complication rates were calculated for all polyps or (polyps > = 20 mm). Perforation and surgery 0.3% (0.5%), Admission post procedure 1.2% (1.9%), Late bleed requiring endoscopy +/− admission 2.4% (3.8%), Late bleed requiring transfusion 0.3% (0.5%), Post-polypectomy syndrome requiring admission 0.3% (0.5%) and Stricture 0.3% (0.5%). Conclusion: The safety and efficacy in this study is similar to that in other published series from western expert centres. The complications rates seem acceptable and provide data to consent with. The higher recurrence rates with lesions >4 cm may be reduced with newer techniques such as endoscopic submucosal dissection. The model of a single endoscopist initially providing an EMR service has worked in our centre and in addition provided a focus for new consultant and senior SpR training.